Child, Church and Protection: A Historical Theology Perspective and Its Implications for Churches in Africa - Ebenezer Tetteh Kpalam (E-Journal of Religious and Theological Studies)
Children have the right to protection. As a result, all institutions, including churches are expected to take concrete steps to safeguard children. There is a growing interest in the role of churches in child protection. Africa is considered the center of vitality of Christianity and Christian faith communities have become a powerful force in African society However, recent data revealed that various forms of violence against children such as sexual, physical, emotional and neglect are rife on the continent. Faith communities have a mandate to undertake concrete measures to ensure the safeguarding of children in churches and society at large. Using a chronological approach to historical theology, the paper undertakes critical reflections on the church’s child protection efforts across the major periods of church history to obtain insights into the contemporary church in Africa. The paper posits that churches can glean valuable lessons from the church age to inform and reform churches’ child protection efforts The paper contributes to the current discourse on efforts of churches on child protection by shedding light on the fact that during the church age, children were viewed as precious in the sight of God and worthy to be nurtured in a caring and loving environment.